Non-invasive ventilation in the treatment of severe polymicrobial community-acquired pneumonia - Enrico Cinque; Ines Maria Grazia Piroddi; Cornelius Barlascini; Alessandro Perazzo; Antonello Nicolini (Italian Journal of Medicine, 2017)
Polymicrobial pneumonia may be caused by the combination of respiratory viruses, bacteria and fungi in a host. Colonization by Streptococcus pneumoniae was associated with increased risk of Intensive Care Unit admission or death in the setting of influenza infection, whereas the colonization by methicillin sensible Staphylococcus aureus co-infection was associated with severe disease and death in adults and children. The principal association of pathogens in community-acquired pneumonia (CAP) is bacteria and viral co-infection, and accounts approximately for 39% of microbiological diagnosed cases of CAP. The differential clinical diagnosis between a viral and a bacterial CAP is not easy: no clinical signs or radiological findings help the clinician to suspect to the diagnosis. Patients with polymicrobial infections are more likely to have underlying medical conditions and have more severe outcome. Severe respiratory failure and need of mechanical ventilation occur in several cases. Non invasive ventilation (NIV) use aims to avoid invasive mechanical ventilation. NIV treatment is controversial owing to high reported treatment failure. In this case series we report three cases of severe polymicrobial CAP: all of them required NIV with a good outcome.